Accuracy of cone beam computed tomography in evaluation of palatal mucosa thickness. (13th February 2020) - Ogawa, Miho; Katagiri, Sayaka; Koyanagi, Tatsuro; Maekawa, Shogo; Shiba, Takahiko; Ohsugi, Yujin; Takeuchi, Yasuo; Ikawa, Takahiro; Takeuchi, Shogo; Sekiuchi, Takayuki; Arai, Yuki; Kazama, Ryunosuke; et al.
Abstract: Aim: The purpose of this study was to investigate the accuracy of the measurement of palatal mucosa thickness using cone beam computed tomography (CBCT) and to create a conversion formula to evaluate palatal mucosa thickness more accurately. We then evaluated the palatal mucosa thickness in a Japanese population using CBCT and the conversion formula. Materials and methods: We evaluated palatal mucosa thickness in 10 healthy subjects at 15 sites using CBCT, digital impression, and K file. Multiple regression analysis was performed to create a conversion formula to measure thickness accurately. We then obtained CBCT data from 174 patients retrospectively, applied the conversion formula, and evaluated palatal mucosa thickness. Results: Sites of measurement affected measurement error. Measurement using CBCT was 0.34 ± 0.04 mm smaller than actual measurement; therefore, a conversion formula was created. Male, age ≥60 years, and probing pocket depth ≥4 mm had significant and positive associations with palatal mucosa thickness; however, no association was observed between bleeding on probing and palatal mucosa thickness. Conclusion: CBCT is useful for the noninvasive and accurate measurement of palatal mucosa thickness.